ANALISIS PENGAMBILAN KEPUTUSAN PETANI DALAM PEREMAJAAN KELAPA SAWIT DI KECAMATAN LONG IKIS KABUPATEN PASER (Analysis of Farmers' Decision Making in Oil Palm Replanting in Long Ikis District, Paser Regency) - DINA LESMANA; FIRDA JUITA; EKO HARRI YULIANTO A; DIAN SAEFUDIN (Universitas Mulawarman (University of Mulawarman), 2022)
The success of farmers in rejuvenation is considered very important for the survival of farmers. Oil palm smallholders are expected to be able to make decisions on rejuvenating their oil palm plantations in time to improve yields and increase farmers' income in the future. The general objectives of this research are to find out (1) how farmers make smallholder decisions in the oil palm rejuvenation program; (2) the factors that influence farmers' decision making in the oil palm rejuvenation program in Long Ikis District, Paser Regency. This research was conducted in Long Ikis District, Paser Regency. Sampling was done by purposive sampling method. Data analysis used descriptive qualitative analysis method using Likert attitude scale measurement. The data are tabulated and interpreted qualitatively with categories. This research is expected to provide information for farmers in making decisions for oil palm rejuvenation programs in order to increase the productivity of oil palm plantations. The things that farmers consider in making decisions about replanting are from the agronomic, economic and social aspects. Of the 6 factors that influence farmers' decisions to replant (land area, plant height, farming experience, income, government assistance and capital) the most influential factors in making oil palm replanting decisions are land area, plant height, capital and government assistance.